Peculiarities of depressive disturbances at cerebral stroke with different lesion focus localization (by neuro-imaging method data) - N. G. Katayeva; A. Yu. Levina (Бюллетень сибирской медицины)
The aim of investigation has been a specification of affective disturbances at patients in acute stroke period depending on the lesion focus. Affective disturbances have been revealed by imaging methods — computed and magnetic resonance tomography (CT or MRT). 72 patients with strokes have been examined (41 women and 31 men). Affective disturbances have been evaluated according to criterions and have been specified with depression self-concept scale of Beck. During the investigation the following conclusions have been made: 1) depressive disturbances of all the patients have had the character of light depressive episode (average mark by Beck scale — 22,14 ± 1,59); 2) depressive disturbance frequency have been significantly greater at stem structure damage than of the right (p < 0,001) and left (p < 0,05) hemispheres; 3) depressive disturbances have been revealed more frequently at single persons (p < 0,05).